The learning curve for endoscopic tympanoplasties: a single-institution experience, in Birmingham, UK. Issue 5 (20th May 2020) - Baruah, P; Lee, J D E; Pickering, C; de Wolf, M J F; Coulson, C
Abstract: Objective: This study aimed to assess whether increasing operative experience results in better surgical outcomes in endoscopic middle-ear surgery. Methods: A retrospective single-institution cohort study was performed. Patients underwent endoscopic tympanoplasty between May 2013 and April 2019 performed by the senior surgeon or a trainee surgeon under direct supervision from the senior surgeon. Following data collection, statistical analysis compared success rates between early (learning curve) surgical procedures and later (experienced) tympanoplasties. Results: In total, 157 patients (86 male, 71 female), with a mean age of 41.6 years, were included. The patients were followed up for an average of 43.2 weeks. The overall primary closure rate was 90.0 per cent. Conclusion: This study demonstrates an early learning curve for endoscopic ear surgery that improves with surgical experience. Adoption of the endoscopic technique did not impair the success rates of tympanoplasty.